2015
DOI: 10.1002/mdc3.12170
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Therapies for Parkinson's Disease: What's Promoted, Rationale, Potential Risks and Benefits

Abstract: Background: Nearly half of all patients with Parkinson's disease (PD) utilize some form of complementary therapy often identified on the Internet and frequently not reported to their physicians. Treating physicians are sometimes unaware of such treatments, including their rationale, mechanisms, potential efficacy, and potential adverse effects. Methods: Methods for this study included systematic Internet search of products recommended for PD, medical literature review to determine scientific rationale, any evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…A recent MDS systematic review concluded that, in PD-MCI, the monoamine oxidase B (MAO-B) inhibitors rasagiline and rivastigmine presented an acceptable risk of adverse events, without specialized monitoring, but there is still insufficient evidence on their efficacy [ 44 ]. Non-pharmacological interventions, including transcranial direct-current stimulation (T-DCS) and cognitive rehabilitation are still under investigation [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent MDS systematic review concluded that, in PD-MCI, the monoamine oxidase B (MAO-B) inhibitors rasagiline and rivastigmine presented an acceptable risk of adverse events, without specialized monitoring, but there is still insufficient evidence on their efficacy [ 44 ]. Non-pharmacological interventions, including transcranial direct-current stimulation (T-DCS) and cognitive rehabilitation are still under investigation [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamins such as beta-carotenes or vitamin B6 also have antioxidant properties, and evidence from two case-control studies shows that they decrease the risk for PD [69,70]. Unsaturated fatty acids and other plant-derived micronutrients reduce proinflammatory cytokine production and may reduce inflammation in these patients [71]. In conclusion, the pro-dopaminergic effect of AtreMorine can be attributed to the rich content of natural L-DOPA (average concentration 20 mg/g) in its composition.…”
Section: Discussionmentioning
confidence: 95%
“…Our search was limited to articles published between 1982 and 2022. Subsequently, we cross-checked our findings with findings reported in some of the most recently published comprehensive reviews on pharmacological treatments or food supplements targeting mitochondrial dysfunction in PD [10,[17][18][19][20][21]. The list of compounds identified is available in Table 1.…”
Section: Methodsmentioning
confidence: 97%